HIV-associated Prospective Memory Impairment in the Laboratory Predicts Failures on a Semi-naturalistic Measure of Health Care Compliance - Zogg, Jennifer B. (2010)
HIV-associated neurocognitive impairment, particularly in the domain of prospective memory (ProM), increases the risk of poor everyday functioning outcomes, including medication non-adherence. However, whether ProM plays a role in health care compliance outside of the realm of medication adherence remains to be determined. This study evaluated the hypothesis that ProM is an independent predictor of failure to comply with non-medication related instructions akin to those commonly given by health care providers. Participants were 139 HIV-infected adults who underwent medical, psychiatric, and neuropsychological assessments, including a laboratory-based measure of ProM. To assess real-world compliance, participants were instructed to call the examiner 24 hours after the evaluation and report how many hours they had slept. Individuals who failed to correctly comply with these instructions (n=104) demonstrated significantly lower performance on both time- and event-based ProM at baseline than the compliant group (n=35), an effect that was primarily driven by errors of omission. ProM remained a significant predictor of noncompliance after controlling for potential confounders, including demographics (e.g., education), traditional cognitive measures of retrospective memory and executive functions, and psychiatric factors (e.g., depression). Results support the hypothesis that ProM plays a unique role in compliance with health care instructions for HIV disease management and may inform interventions designed to improve treatment outcomes.